2011
DOI: 10.1002/lary.21799
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of acoustic neuromas

Abstract: Our review of the literature suggests that near-total or extensive subtotal resection of vestibular schwannomas may confer much improved functional outcomes without significant detriment to acceptable rates of tumor control. However, further follow-up is needed in patients treated with this relatively novel surgical paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 62 publications
0
33
0
3
Order By: Relevance
“…All vestibular schwannomas are managed in a multi-disciplinary team setting with decisions dependent on size of the tumour, the extent of hearing loss, patient co-morbidities and preferences. The principal aim is to minimise morbidity, preserving functions of surrounding structures, particularly the facial nerve [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All vestibular schwannomas are managed in a multi-disciplinary team setting with decisions dependent on size of the tumour, the extent of hearing loss, patient co-morbidities and preferences. The principal aim is to minimise morbidity, preserving functions of surrounding structures, particularly the facial nerve [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst historically the main aim was for complete tumour removal, this has now been superseded with achieving the best patient outcome-by optimising post-operative cranial nerve function whilst safeguarding for tumour re-growth [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, microsurgery cannot achieve the facial and cochlear nerve outcomes of radiosurgery. 78,95 Because functional deficits of the facial nerve lead to physical, cosmetic, and psychological consequences for patients, avoidance of facial nerve palsy is a major goal of VS surgery. 3,31,59 Therefore, it is critical to compare the pre-and postoperative facial nerve function in patients with VS, not only for effective care of these patients, but also to assess the likelihood of functional recovery.…”
mentioning
confidence: 99%
“…95 Moreover, these tumors are generally slow growing, and other adjunctive therapies such as Gamma Knife surgery are available for the residual tumors. In a comparison of 15 patients who underwent subtotal resection of tumors that exceeded 3 cm in diameter with the published results of patients with similarly larger tumors, Raftopoulos et al 74 found that facial nerve dysfunction was 0% in their patients compared with 20%-35% in patients from other published series.…”
mentioning
confidence: 99%
See 1 more Smart Citation